A SYSTEMATIC STUDY OF THE ORIENTAL GENUS ANCYLOTROPUS CAMERON (HYMENOPTERA : EUCHARITIDAE) - NARENDRAN, T.C.; SHEELA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
The rare genus Ancylotropus Cameron was redefined with a diagnosis of the genus. The little known species A. cariniscutis Cameron and A. manipurensis (Clausen) are redescribed and a key to separate the two species is also provided.